2004
DOI: 10.1148/radiol.2322030778
|View full text |Cite
|
Sign up to set email alerts
|

High-b-Value Diffusion-weighted MR Imaging for Pretreatment Prediction and Early Monitoring of Tumor Response to Therapy in Mice

Abstract: High-b-value diffusion-weighted MR imaging has potential use for the early detection of response to therapy and for predicting treatment outcome prior to initiation of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 26 publications
4
109
0
Order By: Relevance
“…12,13 Although the mechanism of rise in the ADC at an early phase of treatment following cytotoxic and radiation treatment in experimental and human tumors is not fully understood, it has been speculated that a rise in ADC might be attributed to an increase in the fractional volume and diffusion of water molecules in the extracellular space that occurs with the disorganized micro- structure in necrosis and apoptosis in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although the mechanism of rise in the ADC at an early phase of treatment following cytotoxic and radiation treatment in experimental and human tumors is not fully understood, it has been speculated that a rise in ADC might be attributed to an increase in the fractional volume and diffusion of water molecules in the extracellular space that occurs with the disorganized micro- structure in necrosis and apoptosis in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Higher b-values may provide better characterisation of PC and treatment response in experimental mouse models [55]. Larger b-values are necessary to limit the effects of bulk motion (perfusion) [56].…”
Section: B-valuementioning
confidence: 99%
“…87 Baseline ADC values may predict the likelihood that a patient will respond to therapy. 88,89 For example, a significantly higher ADC value at baseline has been reported for nonresponding patients with rectal adenocarcinomas compared with the value for patients who responded to chemotherapy and chemoradiation. 89 However, the prognostic implications of the pretreatment ADC values Original Article require further validation.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…90 An increase in ADC values as a result of therapyinduced tumor cell lysis and necrosis has been demonstrated in both preclinical and clinical studies. 88 Changes in ADC values may precede those in tumor volume, making DWI a potential biomarker for early response to therapy. Furthermore, several studies have demonstrated a positive association between therapy-induced elevation in ADC values and better clinical outcomes to a variety of antitumor therapies.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%